(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Meningioma is an extracerebral, mostly benign tumor originating from the dura mater, less commonly from the pia mater of the brain and spinal cord, and rarely from the choroid plexuses of the cerebral ventricles or arising ectopically in the bones of the skull, spine, and along the nerve roots [1, 2, 3]. Meningiomas account for approximately one third of all intracranial tumors. The incidence of meningiomas is 6.58 per 100,000 population per year. This indicator increases with age, which, given the aging population of developed countries, further increases the significance of the problem [4, 5, 6]. In individuals aged 35 years and older, meningioma is the most common CNS tumor. Currently, the prevalence of meningiomas is 97.5 per 100,000 population. It should be noted that, despite the benign course, 30–45% of these neoplasms spread to the base of the skull. The localization of the tumor always determines the clinical symptoms of the disease, the course of the disease, and, to a large extent, the prognosis of surgical treatment [7].